Faktor - Faktor yang Mempengaruhi Kemampuan Auditor dalam Mendeteksi Kecurangan - Dhea Lathifah Aisyahakim; Linda Hetri Suriyanti; Rudi Syaf Putra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
In the rapid development of the era that provides convenience to humans through technology. However, with the convenience obtained, some people commit fraud for personal or group gain, so to prevent fraud, fraud detection needs to be carried out by auditors. This study is a quantitative study that aims to determine whether professional skepticism, independence, auditor experience, competence, and audit training have a partial influence on the auditor's ability to detect fraud. The sample in this study was 76. The sample determination used the Non Probability Sampling technique. The data collection technique was by distributing and distributing questionnaires to the BPKP Riau Province Representative auditors directly. In analyzing this, validity and reliability tests, classical assumption tests, linear regression tests, and t tests were used. The research data processing used SPSS version 22. The results of the study showed that professional skepticism, independence, auditor experience, audit training did not affect the auditor's ability, and competence affected the auditor's ability to detect fraud.